Cystadenoma: a rare tumor originated in minor salivary gland Cistadenoma: um tumor raro em glândula salivar menor - Jean Nunes dos Santos; Adna Conceição Barros; Viviane Almeida Sarmento; Clarissa Araújo Silva Gurgel; Veronica Ferreira de Souza (Sociedade Brasileira de Patologia Clínica, 2008)
Cystadenoma of salivary glands is an uncommon benign neoplasm that presents intraluminal papillary projections. The authors describe one case of cystadenoma located in the buccal mucosa and highlight its histomorphological features and differential diagnosis. O cistadenoma de glândula salivar é uma neoplasia benigna incomum, que exibe projeções papilíferas intraluminais. Os autores descrevem um caso de cistadenoma localizado na mucosa jugal, discutindo os aspectos histomorfológicos e o diagnóstico diferencial desse tumor.